2021
DOI: 10.47405/mjssh.v6i11.1145
|View full text |Cite
|
Sign up to set email alerts
|

Online Purchasing Behaviour of Consumers at Zalora in Malaysia

Abstract: In the 1960s, the emergence of technology introduced by humans spurred the establishment of the Internet that can engage all people globally. Since 1994, the Internet has contributed tremendously towards the evolution of online shopping through the development Electronic Commerce (EC). There are many online shopping websites that have been established by various companies as other alternatives for consumers to purchase their goods or services rather than shopping at the stores. In Malaysia, the reputation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…As a result, the premise of the link between online design and client purchasing is approved in Zalora's Malaysia application. Previous researchers' hypotheses (Aznor et al, 2021), which confirm the findings of our study are that when customers perceive high-quality site design, they are more likely to purchase. The quality of a website has a direct influence on behaviour intention.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As a result, the premise of the link between online design and client purchasing is approved in Zalora's Malaysia application. Previous researchers' hypotheses (Aznor et al, 2021), which confirm the findings of our study are that when customers perceive high-quality site design, they are more likely to purchase. The quality of a website has a direct influence on behaviour intention.…”
Section: Discussionsupporting
confidence: 91%
“…According to Sari, Manggabarani, and Husniati (2020) and Aznor, Ramli, Zamri, Nye, Basri, Khalid, Shaharin, Ramiah, Paramasivam, and Krishnan (2021), the brand image of a company is determinants for consumers to purchase products or services. As explained by Aznor et al (2021), Zalora Malaysia has a good brand image, especially on fashion online shopping platforms. In recent, the present societal trend of making online purchases resulted from the number of applications that provide online shopping platforms is growing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also demonstrated a significant relationship between website design and purchasing behaviour of online customers in Klang Valley. Hence, this study supports the previous research by (Aznor et al, 2021;Cho & Park, 2001;Rita et al, 2019;Prashar et al, 2017;Prastiwi & Fitria, 2021;Akram et al, 2018;Rahi et al, 2017), who have agreed upon the significant influence of website design towards online purchasing behaviour. According to scholars, it has been shown that consumers' comfort and trust in the merchant greatly affected their intention to shop online.…”
Section: Discussionsupporting
confidence: 91%
“…According to the e-Commerce Foundation, consumers research products online or in-store before making an online or in-store purchase. As a result, website today is increasingly relevant for businesses of all sizes and types, owing to the changing buying behaviour (Aznor et al, 2021). For any online store to attract customers, the quality of website design is extremely significant.…”
Section: Relationship Between Website Design and Online Purchasing Be...mentioning
confidence: 99%